A Randomized, Placebo-controlled Trial of the Analgesic Efficacy and Safety of the p38 MAP Kinase Inhibitor, Losmapimod, in Patients With Neuropathic Pain From Lumbosacral Radiculopathy. Issue 4 (April 2015) - Ostenfeld, Thor; Krishen, Alok; Lai, Robert Y.; Bullman, Jonathan; Green, Joanne; Anand, Praveen; Scholz, Joachim; Kelly, Madeline
Abstract : Objectives: Preclinical studies have demonstrated involvement of p38 mitogen-activated protein kinase signaling pathways in the development of persistent pain after peripheral nerve injury. A double-blind, randomized, placebo-controlled study was undertaken to evaluate the analgesic efficacy of losmapimod (GW856553), a novel p38α/β inhibitor, in patients with chronic neuropathic pain due to lumbosacral radiculopathy. Materials and Methods: A total of 144 patients with at least moderate baseline pain intensity (average daily score of ≥4 on an 11-point pain intensity numeric rating scale) were randomized to receive losmapimod, 7.5 mg bid orally or placebo. All patients underwent a blinded placebo run-in period for 7 days before receiving losmapimod/placebo for 28 days. Efficacy and safety evaluations were undertaken weekly. Results: The adjusted mean treatment difference for the change from baseline to week 4 in numeric rating scale was −0.36 U (95% confidence interval, −0.84, 0.13; P =0.149) in favor of losmapimod over placebo; this was not considered clinically meaningful. Statistically significant differences in favor of losmapimod were observed, however, for several secondary endpoints of emotional, physical, and social functioning: Oswestry Disability Index; Profile of Mood States total score; Short-Form 36 Health Survey physical functioning, bodily pain, general health, role emotional, social functioning, and vitality domains; and Short-Form 36 physical, and mental components. There were no unexpected findings related to safety or tolerability following treatment with losmapimod. Discussion: Losmapimod could not be differentiated from placebo in terms of analgesia. The lack of response could reflect insufficient losmapimod levels in the spinal cord or differences between lumbosacral radiculopathy and animal models of neuropathic pain. Abstract : Supplemental Digital Content is available in the text.